DESIGN OF AUTOMATIC PACKING SYSTEM FOR PIPETTE SUCTION HEADS - Sun,Lixiang (2022)
ABSTRACT Among the shortcomings of the existing pipette cartoning technology, first, it needs a lot of manpower and time to complete by hand; second, it is based on a semi-automatic equipment for loading the suction heads, which cannot ensure that the suction head is upright (bottom tip down) or avoid the phenomenon of suction head overlapping. Based on this, an automatic system for packing pipette suction heads is proposed. Firstly, the research status of pipette cartoning is analyzed; secondly, the mechanical design of the automatic cartoning system for pipette suction heads is given; thirdly, the hardware structure diagram and software flow of the automatic cartoning system are given. Finally, the system is applied to a pipette suction head box in a school laboratory. After many times of practice, it is proved that the system can realize the automatic pipette suction head box, and has the advantages of stable performance, accurate positioning and intuitive display, which improves the efficiency of the pipette suction head box in the laboratory.